MicroRNAs mediated targeting on the Yin-yang dynamics of DNA methylation in disease and development. (October 2015) - Tu, Jiajie; Liao, Jinyue; Luk, Alfred Chun Shui; Tang, Nelson Leung Sang; Chan, Wai-Yee; Lee, Tin-Lap
Abstract: For decades, DNA methylation at the 5 position of cytosine (5mC) catalyzed by DNA methyltransferases (DNMTs) is a well-known epigenetic modification in mammalian genome, where it modulates chromatin remodeling and transcriptional silencing. The discovery of Ten-eleven translocation (TET) enzymes that oxidize 5mC to 5-hydroxymethylcytosine (5hmC) prompts a new era of DNA demethylation research. It is now established that in DNA demethylation pathway 5mC is first converted to 5-hydroxymethylcytosine (5hmC), then 5-formylcytosine (5fC) and 5-carboxylcytosine (5caC) through TETs. Conversion to unmethylated cytosine (5C) is further facilitated by excision mechanism through thymine-DNA glycosylase (TDG) or base excision repair (BER) pathway. Our understanding of DNMTs and TETs on epigenetic dynamics of cytosine methylation has led to a completion of the methylation (Yin) – demethylation (Yang) cycle on epigenetic modifications on cytosine. However, the regulations on DNA demethylation pathway remain largely unknown. In this review, we provide the recent advances on epigenetic dynamics of DNA demethylation and its potential control from the prespective of small non-coding RNA-mediated regulation. Specifically, we will illustrate how microRNAs contribute to active DNA demethylation control in normal and disease development based on recent findings in stem cells and cancer. This article is part of a Directed Issue entitled: Epigenetics dynamics in development and disease.